Probiotics – potential successors to antibiotics for infectious diseases? A narrative review - Simi Shantanu Paknikar; N Sarala (Journal of Current Research in Scientific Medicine)
Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host. Commonly used probiotics in humans belong to the genera Bifidobacterium, Lactobacillus, Bacillus, Streptococcus, and Saccharomyces and are available as single agents or in a combination. They have been used for the treatment of several conditions, but data regarding their efficacy are often inadequate. There is some evidence of the use of probiotics for bacterial infections. The objective of this narrative review is to present the status of probiotics in the prevention and treatment of bacterial infections, along with their possible mechanisms of action and adverse effects related to their use. Information was obtained through a literature search of PubMed-indexed articles over the past 11 years and a Google search. Based on our findings, we concluded that probiotics may be more useful in the prevention of recurrent infections such as Clostridioides difficile infection or prevention of adverse effects caused by antibiotics rather than treating infections. This review could provide insights and guidance for physicians regarding the appropriate use of probiotics in bacterial infections.